THE USE OF MIND MAPPING TECHNIQUE ON STUDENTS ABILITY TO WRITE A RECOUNT TEXT - Hartiwi, Ani; Sutisna, Entis; Kurniati, Nur Utami Sariat (Journal of English Teaching and Linguistics Studies (JET Li), 2019)
Writing is one of the language skills that should be mastered by the students. According to pre research observation, they still got some difficulties when they were asked to write English text. Developing ideas is one of their difficulties in writing. Hence, an appropriate technique is required to help students overcome this problem. This study is conducted to find out the effect of using mind mapping technique on studentsâ€Ÿ ability to write a recount text. Pre Experimental method and One Group pretest-posttest design are used in this study. First grade students of SMA Negeri 1 Cigombong are chosen as the sample. They are 32 students, all in one class. Purposive sampling technique is used to choose the sample. The data are collected through pre-test and post-test in the form of writing test. Then, t-test is used to analyze the data. The result of analysis shows that the value of t -test is 23.29 and the value of t-table at  0.05 level of significance is 2.04. This indicates that the value of t - calculated  is  higher  than  t-table,  hence  null  hypothesis  is  rejected  and  alternative  hypothesis  is accepted. Thus, it is concluded that there is an effect of using mind mapping technique on studentsâ€Ÿ ability to write a recount text. Keywords: Writing ability, Recount text, Mind mapping technique.